Impacts of human resources management strategies and practices on workers performance in construction industry: a review - Maliha, Mohammed N.; Tayeh, Bassam A.; Abu Aisheh, Yazan Issa (Journal of Civil Engineering and Management, 2025)
Human resource management (HRM) plays a vital role in the growth and sustainability of companies and in achieving company objectives, as HRM relates to the workers’ practices and their functional roles. The main objective of this paper is to identify the HRM strategies, practices and their impact on worker’s performance in the Architecture, Engineering, and Construction (AEC) Industry. The method which was used in this study was based on three stages. After the completion of the database and web engine search, the total number of sources found were 149. Next, the sources’ titles and abstracts were reviewed and those marked as relevant to the review were chosen to be retrieved and thoroughly reviewed. The sources were chosen based on the following inclusion criteria: (a) the sources implied in HRM strategies in the AEC industry, (b) the sources released between 2010 and 2023, (c) the online sources, and (d) the English-language sources. Also, the selected sources are reviewed to extract the factors using the content analysis method which is a thorough and systematic study of the contents of a specific body of material. In addition, content analysis is carried out to extract practices of HRM strategies and their impact on worker performance. This can be followed up and observed through the figures and tables that come later. As a final result, which concludes the outputs of the previous stages which results in a first-round total of 31 HRM strategies practice but in the second-round result of reaching 39 different sources from 149 related sources. After that, discussing the most popular between them based on the appearance of it in the sources which reviewed beside that, the impact of it on worker’s performance were viewed in the AEC industry. Based on that, it was found the following 5 categories of strategies: (1) Human Resources Planning; (2) Polarization and Recruitment; (3) Training and Development; (4) Human Resources Following-up; (5) Career Planning. At the same time the most popular practices are based on appearance in sources: In terms of Human Resources Planning Strategy, “The company’s management analyses the functions accurately”. In Polarization and Recruitment Strategy, “The company’s internal resources are the best to provide its human resource needs” and “Selection and recruitment policies are in line with the company’s current and future needs”. In Training and Development of Human Resources Strategy, “The company evaluates the results of development and training programs to achieve the purpose of feedback”. In Human Resources Following-up Strategy, “There is a fair incentive system in the company”. In Career Planning Strategy, “There is a clear description of the relationship of workers to each other”. Finally, human resource management strategies and practices are one of the major players in the AEC industry, which is evidenced by its impact on the performance of workers.First published online 22 October 2024